Sermonis brevitas amica. O długości kazania dawniej i dziś - Radej, Maciej (Analecta Cracoviensia, 2011)
The article is an analysis on the length of a sermon in the history of preaching. For centuries, it has been emphasized that conciseness is a friend of a sermon (sermonis brevitas amica) and a lot should be said just in a few words (multa in paucis) and - according to the Council of Trident - people should be preached "briefly and accessibly" (cum brevitate et facilitate sermonis). As an effect, there was a gradual reduction of sermons which in previous centuries were given for many hours into a ten minute Sunday homily which is expected nowadays. At the same time an interesting phenomena can be observed, namely that the very listeners would like to listen to longer sermons while retreat, concentration days or other important ceremonies during which they expect to be given deeper arguments on faith and moral life. Listeners do not feel bored with the length of a sermon if it is given by a charismatic preacher speaking with a great belief and passion.